1H,3H-Imidazolium (R,S)-camphor-10-sulfonate - Abdul Rahman, Mohd Basyaruddin; Omar, Emmy Maryati; Ng, Shie Ling; Kia, Reza; Fun, Hoong Kun (International Union of Crystallography, 2009)
The title compound, C(3)H(5)N(2) (+)·C(10)H(15)O(4)S(-), comprises two crystallographically independent ion pairs (A and B) in the asymmetric unit with slightly different conformations due to the disordered methyl groups in the anion of molecule A. Two intra-molecular C-H⋯O hydrogen bonds generate S(6) ring motifs. In mol-ecule A, the methyl groups are disordered over two sets of positions with a site-ocuppancy ratio of 0.547 (9):0.453 (9). Extensive inter-molecular N-H⋯O and C-H⋯O hydrogen-bonding inter-actions occur in the crystal structure which link the mol-ecules into a two-dimensional network parallel to the (100) plane.